The role of mitochondria-associated membranes mediated ROS on NLRP3 inflammasome in cardiovascular diseases - Zhao, Jiahao; Li, Junli; Li, Guoyong; Chen, Mao (Frontiers in Cardiovascular Medicine, 2022)
Abstract Reactive oxygen species (ROS) metabolism is essential for the homeostasis of cells. Appropriate production of ROS is an important signaling molecule, but excessive ROS production can damage cells. ROS and ROS-associated proteins can act as damage associated molecular pattern molecules (DAMPs) to activate the NOD-like receptor thermal protein domain associated protein 3 (NLRP3) inflammasome in cardiovascular diseases. Previous studies have shown that there are connected sites, termed mitochondria-associated membranes (MAMs), between mitochondria and the endoplasmic reticulum. In cardiovascular disease progression, MAMs play multiple roles, the most important of which is the ability to mediate ROS generation, which in turn further activates the NLPR3 inflammasome, exacerbating disease. In this review, the following topics will be covered: 1. Molecular structures on MAMs that can mediate ROS generation; 2. Specific mechanisms of molecule-mediated ROS generation and the molecules' roles in cardiovascular disease, 3. The effects of MAMs-mediated ROS on the NLRP3 inflammasome in cardiovascular disease. The purpose of this review is to provide a basis for subsequent clinical treatment development.